The Mediation of City Branding Identity: An Analysis of Aesthetic Elements in Surakarta's Iconic Architecture - Marinda Noor Fajrina Noviana Putri; Retna Hidayah; Pita Asih Bekti Cahyani (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
Landmark buildings often serve as the most powerful visual representations of a city. However, the ways in which the visual qualities of architecture operate in shaping city branding remain insufficiently examined. Recent scholarship increasingly highlights the importance of architecture in constructing urban identity. Nevertheless, specific investigations into the aesthetic criteria of iconic buildings—particularly colour, ornament, and form—as factors that influence visitors’ perceptions and place memory are still relatively limited. This study addresses this gap by proposing an analytical framework that connects architectural aesthetics to the core dimensions of city branding. Using a qualitative digital etnographic approach, this research develops an Aesthetic–Branding Analysis Framework to map particular visual attributes to branding outcomes, including identity, representation, and experiential quality within the digital dimension. The findings indicate that aesthetic elements are not merely decorative features, but actively communicate meaning and shape visitors’ expectations of a place. Building on these results, the study proposes a Conceptual Model of Aesthetic-Based Branding Formation, illustrating how architectural visuals interact with collective perceptions and urban narratives through ongoing reciprocal processes, ultimately producing shared meanings over time. Theoretically, this study reinforces the argument that aesthetic decisions—often treated as secondary or supportive aspects—can function as key drivers in forming urban character and reputation. Practically, the findings encourage more strategic investment in iconic architecture as a tool for city brand communication, strengthen the rationale for heritage preservation beyond cultural considerations alone, and support the systematic integration of aesthetic factors as essential components of urban planning and development.